Preliminary Investigation of LED Lighting as Growth Light for Seedlings from Different Tree Species in Growth Chambers - ASTOLFI, Stefania; MARIANELLO, Chiara; GREGO, Stefano; BELLAROSA, Rosanna (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2012)
The influence of light quality on growth and metabolic activity during pre-cultivation (in miniplug containers) of beech (Fagus sylvatica L.), holm oak (Quercus ilex L.) and wild cherry (Prunus avium) plants was investigated. Seedlings were grown in a growth chamber for a month under light-emitting diode (LED) light or fluorescent light. The LED lamps (Valoya) used in this study emitted a continuous spectrum thanks to a mixture of blue, green, red and far-red LEDs. Our results showed that plant response to light quality seems to be related to the plant species. In particular, in beech seedlings fresh and dry weight, shoot height and leaf area were greatest when plants were cultured under LED light, and lowest under fluorescent lamps. Furthermore, we found that LED-induced reduction of chlorophyll contents in beech and holm oak leaves resulted in an increase of the carboxylase capacity of Rubisco in the same plant species suggesting an improvement of light-use-efficiency in these plants. These results indicate that LED light may be suitable for the culture of plants in tightly controlled environments. The comparison of malondialdehyde levels between LED and fluorescent grown plants strongly supports this idea.
Keywords: beech; glutamine synthetase; Holm oak; light; lipid peroxidation; Rubisco; wild cherry

Photosynthesis, Soluble and Structural Carbon Compounds in Two Mediterranean Oak Species (Quercus pubescens and Q. ilex) after Lifetime Growth at Naturally Elevated CO2 Concentrations - Blaschke, L.; Schulte, M.; Raschi, A.; Slee, N.; Rennenberg, H.; Polle, A. (Plant Biology, 2001)
Abstract: To study physiological responses of mature forest trees to elevated CO2 after lifetime growth under elevated atmospheric CO2 concentrations (pCO2), photosynthesis, Rubisco content, foliar concentrations of soluble sugars and starch, sugar concentrations in transport tissues (phloem and xylem), structural biomass, and lignin in leaves and branches were investigated in 30- to 50-year-old Quercus pubescens and Q. ilex trees grown at two naturally elevated CO2 springs in Italy. Ribulose-1,5-bisphosphate carboxylase/oxygenase content was decreased in Q. pubescens grown under elevated CO2 concentrations, but not in Q. ilex. Photosynthesis was consistently higher in Q. pubescens grown at elevated CO2 as compared with “control” sites, whereas the response in Q. ilex was less pronounced. Stomatal conductance was lower in both species leading to decreased transpiration and increased instantaneous water use efficiency in Q. pubescens. Overall mean sugar + starch concentrations of the leaves were not affected by elevated pCO2, but phloem exudates contained higher concentrations of soluble sugars. This finding suggests increased transport to sinks. Qualitative changes in major carbon-bearing compounds, such as structural biomass and lignins, were only found in bark but not in other tissues. These results support the concept that the maintenance of increased rates of photosynthesis after long-term acclimation to elevated pCO2 provides a means of optimization of water relations under arid climatic conditions but does not cause an increase in aboveground carbon sequestration per unit of tissue in Mediterranean oak species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Carbohydrate; climate change; Elevated CO2; Lignin; photosynthesis; Rubisco